Analysis of Linear Regression Model with Backward Method For Application of Good Corporate Governance Principles at PT. Asuransi Jasa Indonesia Medan Branch Office - Inggrid Nathalia (JMEA : Journal of Mathematics Education and Application, 2023)
Risk is one of the problems in human life that can make people feel uncomfortable. Various kinds of business that humans will be done by humans to be able to anticipate risks, one of which is by way of insurance. The development of insurance in Indonesia is inseparable from the performance of employee and a Good Corporate Governance system, so that State-Owned Enterprises (BUMN) implement Good Corporate Governance, such as at PT. Asuransi Jasa Indonesia Medan Branch Office. This research was conducted by giving questionnaires to the employees of PT. Asuransi Jasa Indonesia Medan Branch Office on April 1, 2022 at 12.30 WIB. In this study, there are two most influential factors, namely the independency factor and the fairness factor, so that the estimator equation model using the backward elimination method is where is the independency factors and is the fairness factor.